Cultural Geography Perspectives on the Dayak Hampang Uplands-Meratus Mountains, Indonesia - Nasruddin Nasruddin; Mohd Hairy Ibrahim; Muhamad Rusmin Nuryadin; Selamat Riadi (JURNAL GEOGRAFI, 2026)
This study examines the cultural geography of the Dayak Hampang community in the Meratus Mountains by integrating spatial, environmental, and political-economic perspectives. It employs a quasi-qualitative approach supported by survey methods and descriptive analysis to operationalize a cultural geography framework. Qualitative data on cultural values, indigenous knowledge, and settlement toponymy were collected through in-depth interviews. Settlement patterns were analyzed using Nearest Neighbour Analysis, GIS, field surveys, and documentation. The findings reveal that clustered toponymy and settlement patterns reflect a strong socio-spatial attachment to rivers, forests, and cultivated land, forming an integrated cultural landscape rooted in customary institutions. Shifting cultivation and ritual practices function as adaptive socio-ecological strategies that sustain livelihoods and conserve the mountainous environment despite pressures associated with protected forest designation. The study demonstrates that socio-ecological resilience increases when customary governance is formally recognized by reclassifying protected forests as customary forests (hutan adat). Conversely, restrictive state forest regimes that limit community Access, Assets, and Activities (3A) weaken adaptive capacity and heighten ecological vulnerability. Accordingly, the Sustainable Cultural Geography (SCG) model is expressed as: SCG = f (Ecological Resilience, Customary Forest Tenure, 3A Capacity), positioning cultural landscape sustainability as a function of these interrelated components.